Belonging and participation as portrayed in the curriculum guidelines of five European countries - Piškur, Barbara; Takala, Marjatta; Berge, Anita; Eek-Karlsson, Liselotte; Ólafsdóttir, Sara M.; Meuser, Sarah (Journal of Curriculum Studies, 2021)
This study seeks to explore how the belonging and participation, as well as its related concepts, are framed in the national curriculum guidelines of the Netherlands, Finland, Iceland, Norway, and Sweden. We employed a scoping study with concept-mapping methodology. The results reveal macro level principles related to human rights and values, multiliteracy and language, policy measures and ideologies. Meso level principles stressed that education is supposed to guarantee a child’s overall development and skills acquisition, participation involvement in the activities related to a child’s environment and cultural heritage. The micro level principles were indicative of the need for inclusive and accessible physical and social environments, along with teaching methods which foster positive attitudes about diversity and teachers’ expertise levels to address diversity. We also found the importance of designing opportunities that encourage socializing, building relationships, and belongingness. Additionally, the results show how frequently the chosen key concepts are represented in the guidelines. Based on our study we can conclude that curriculum guidelines do not provide sufficent frameworks for promoting children’s belonging and participation. Further exploration on those concepts is needed, along with increased scholarly attention within the spheres of ECEC and compulsory education practice to enable inclusion for all children. publishedVersion